Acute Toxicity Test of Black Pomegranate Peel Extract (Granati Fructus Cortex) Against Larvae of Shrimp (Artemia salina Leach) - Rofiatu Sholihah Achmad; Lingga Aditya Aditya; Nosa Ika Cahyariza (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2019)
Toxicity test on red pomegranate has done, while in black pomegranate is not widely known. Black pomegranate peel (Granati Fructus Cortex) has some chemical ingredients such as saponins, flavonoids, tannins, and alkaloids. Alkaloids, saponins, and flavonoids are thought to be toxic at certain levels. This study aimed to determine the effects of toxic black pomegranate peel extract (Granati Fructus Cortex) against larvae of shrimp (Artemia salina Leach) indicated LC50 values below 1000 µg / ml. This study is purely experimental by using Brine Shrimp Lethality Test (BSLT). The experiments divided into five groups, namely ethanol extract of black pomegranate peel (Granati Fructus Cortex) with a concentration of 100, 150, 200, 250 ppm, and negative control (seawater). Mortality data percentage of Artemia salina Leach analyzed by probit analysis. Results showed that the extract of black pomegranate peel (Granati Fructus Cortex) has a toxic effect on larvae of Artemia salina Leach with LC50 values of 114.090 µg/ml. From these results, it can conclude that black pomegranate peel extract has a potential acute toxic to larval shrimp (Artemia salina Leach) with Brine Shrimp Lethality Test (BSLT) method.